Reproductive endocrine phenotypes relating to CHD7 mutations in humans. Issue 4 (20th November 2017) - Balasubramanian, Ravikumar; Crowley, William F.
Abstract : Mutations in the gene CHD7 cause CHARGE syndrome, a rare multi‐organ syndromic disorder. Gonadal defects are common in individuals with CHARGE syndrome (seen in ∼60–80% of cases) and represent the letter "G" in the CHARGE syndrome acronym. The gonadal defect in CHARGE syndrome results from congenital deficiency of the hypothalamic hormone Gonadotropin‐releasing hormone (GnRH), which manifests clinically as pubertal failure and infertility, and biochemically as hypogonadotropic hypogonadism (low sex steroid hormone levels with inappropriately normal or low gonadotropin levels). In addition to the gonadal endocrine abnormalities, in a small minority of individuals with CHARGE, additional endocrine defects including growth hormone deficiency, multiple pituitary hormone deficits and primary hypothyroidism may also be seen. CHD7 mutations disrupt the targeting of olfactory axons and the migration of GnRH‐synthesizing neurons during embryonic development, resulting in congenital idiopathic hypogonadotropic hypogonadism (IHH) and anosmia (or hyposmia), two features that define human Kallmann syndrome. Since Kallmann syndrome is one of the constituent phenotypes within CHARGE, recent studies have investigated the role of CHD7 mutations in individuals with IHH and established that deleterious missense mutations in CHD7 are associated with Kallmann syndrome as well as normosmic form of IHH. These missense mutations affect the ATPase and nucleosome remodeling activities of the CHD7 protein. These observations suggest that CHD7 protein function is critical for the ontogeny of GnRH neurons and neuroendocrine regulation of GnRH secretion.